Usefulness of a Vascular Clipping System to Create an Arteriovenous Fistula - Jin Suk Lee; Kuk-Jin Nam; Sam-Youl Yoon; Kun Ok Lee; Hyung Joon Han; Sung-Jin Cho; Jong-Woong Park; Tae Jin Song (Journal of Acute Care Surgery, 2020)
Purpose The vascular clipping system (VCS) is beneficial as it is simple and easy to apply for microvascular suturing. Arteriovenous fistula (AVF) creation is a very basic standard technique of microvascular surgery. In this study the VCS and the conventional suture methods were compared in a rabbit model using the carotid artery and vein to create an AVF. Methods There were 28 rabbits assigned equally into 2 groups using the AVF creation method (conventional suturing or the VCS procedure). Histopathology was performed on fixed samples. The procedure time of the 2 methods and changes in histopathology of tissue samples after surgery were compared. Results The VCS procedure showed a lower degree of fibrosis and hyperplasia histologically compared with the conventional suture method. The VCS was quicker to perform and no significant anastomosis stricture was observed. Conclusion In a rabbit model of AVF, the VCS has benefits over the conventional suture method. The VCS provides comparable patency rates, produces fewer side effects such as fibrosis and hyperplasia, and takes less operation time than suturing. The VCS is expected to be useful for cases where renal patients need periodic hemodialysis and thus repetitive access to a vessel.